2008
DOI: 10.1021/jf0730338
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Kinetics of Degradation and Epimerization of Epigallocatechin Gallate (EGCG) in Aqueous System over a Wide Temperature Range

Abstract: (-)-Epigallocatechin gallate (EGCG) is the most abundant catechin in green tea, which has been linked with many health benefits. To ensure the conceivable health benefits from thermally processed products, a kinetic study on the stability of (-)-EGCG in aqueous system was carried out using a HPLC-UV system and Matlab programming. Simultaneous degradation and epimerization of (-)-EGCG were characterized during isothermal reactions at low temperatures (25-100 degrees C) combined with previously conducted experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
182
1
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(202 citation statements)
references
References 27 publications
12
182
1
7
Order By: Relevance
“…These observations are in correspondence with other results published in literature that indicate high extraction temperatures improve extraction efficiencies because the heat renders the cell walls more permeable to solvents and components and increases the solubility and diffusion coefficients of the tea components to be extracted (Vuong et al 2011). However, excessive extraction temperatures above 80°C can cause degradation of the catechins by promoting the change in epistructured catechins to non-epistructured catechins (Wang et al 2008). They indicated that the content of non-epistructured catechins (i.e.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…These observations are in correspondence with other results published in literature that indicate high extraction temperatures improve extraction efficiencies because the heat renders the cell walls more permeable to solvents and components and increases the solubility and diffusion coefficients of the tea components to be extracted (Vuong et al 2011). However, excessive extraction temperatures above 80°C can cause degradation of the catechins by promoting the change in epistructured catechins to non-epistructured catechins (Wang et al 2008). They indicated that the content of non-epistructured catechins (i.e.…”
Section: Resultssupporting
confidence: 79%
“…Epimerization can occur at high temperatures. Wang et al (2008) reported that the concentration of catechins decreased while their isomers increased at increasing temperatures. Degradation of catechins was evident as there was a declining trend in total catechins with increasing temperature.…”
Section: Major Green Tea Catechins Are: (−)-Epicatechin (Ec) (−)-Ementioning
confidence: 99%
“…In addition, the galloylated catechins EGCG and ECG (Fig. 3), but not (ϩ)-gallocatechin-3-gallate (GCG), were detected by the two-step enzyme assay via TLC and HPLC (data not shown), which indicated that the cis-catechins EGC and EC were appropriate substrates of a galloyltransferase instead of the trans-catechin GC or C. These data further confirmed that EGCG and ECG in the tea plant are biosynthesized via enzymatic galloylation of EGC and EC with ␤G, whereas GCG in green tea beverages is derived from isomerization of EGCG during green tea production (33).…”
Section: Evidence For Biosynthetic Enzymes Of Galloylated Catechins-supporting
confidence: 63%
“…Os menores valores encontrados para a epicatequina na infusão podem estar relacionados a possíveis processos de degradação (OSZMIANSKI et al, 1996;JIANG, 2008). Isso também foi observado em nossos ensaios (Seção 4.5).…”
Section: Recuperação (Exatidão)unclassified
“…Embora a epimerização das catequinas seja mais lenta em soluções ácidas, a temperaturas acima de 40 o C podem provocar degradação ou polimerização das mesmas JIANG, 2008). Além disso, metais podem catalizar a degradação de catequinas em meio aquoso (OSZMIANSKI et al, 1996).…”
Section: Avaliação Da Epimerização De Catequinas Durante a Preparaçãounclassified